Comparative Study on the Effect of Heat Treatment and Sonication on the Quality of Barberry (Berberis Vulgaris) Juice. Issue 3 (4th July 2016) - Farhadi Chitgar, Muhammd; Aalami, Mehran; Maghsoudlou, Yahya; Milani, Elnaz
Abstract: Barberry ( Berberis vulgaris ) is an indigenous Iranian plant which its fruit is mainly consumed as fresh, dried and also used for juice production. The objective of this study was to compare the effect of thermal treatment and different sonication conditions on the characteristics of barberry juice. Additionally, the effect of both treatments on degradation kinetics of anthocyanins during refrigerated storage (at 4C) was also evaluated. Sonication and thermal treatments significantly ( P < 0.05) reduced microbial counts. A significant increase in the total phenol content and antioxidant activity in all the sonicated juice samples was observed while the thermal treatment had adverse effect on these parameters. Sonication (especially in 70% amplitude) showed less effect on total anthocyanin and color of barberry juice compared to thermal treatment. The degradation kinetics of anthocyanins in all juice samples during refrigerated storage followed first‐order kinetics. Half‐life ( t 1/2 ) of anthocyanins was much shorter in thermal treatment sample (64.90 days) comparing with sonication samples (111.33–158.58 days). Practical Application: In recent years, emerging non‐thermal techniques, such as sonication, for inactivating microorganisms and improving the health related compounds and other quality parameters of fruit juices have been developed in food industry. Barberry ( Berberis vulgaris ) is a new source of anthocyanins and antioxidant compounds which can be used as natural pigments in the industry. In this study the effects of thermal pasteurization and sonication on microbial growth and some important quality parameters of barberry juice were compared. The information obtained in our study will be useful for successful application of sonication treatment of barberry juice for preserving the quality of this product.